Edirne 1563: A Case of Ilhad in the Shade of False Witnesses - Telci, Cahit (Journal of Alevism-Bektashism Studies, 2019)
One of the most important components of Ottoman social life is component that has been called Alevism for almost two hundred years. Ottoman administration attached importance to Sunni policies especially in the axis of political rivalry with the Safavid Dynasty. It is possible to state that Ottoman administration, especially with the period of Suleiman the Magnificent, followed a regime that prioritised Sunni politics and constantly tried to control non-Sunni components. Ottoman administration kept a close eye on the relations with non-Sunni tendencies of persons who were literate and therefore had a potential to influence their circles. Hence, concepts such as “ilhad”, “zendeka” and “rafz”, which define the non-Sunni sphere, should be considered as products of political reasons, although they carry religious motifs.While Ottoman administration fought rigorously against such intellectual tendencies by using the provincial forces from time to time, sometimes it used the inspection and law mechanisms, as in the case mentioned here.Unfortunately, within the extant texts, the number of procedure texts that show how such ideas or tendencies were interrogated does not exceed the fingers of one hand. This case study, which is a bit more extensive than its counterparts, on the one hand presents the arguments used in the context of the subject, and on the other hand shows how a complaint about “ilhad” was followed in Ottoman legal practice, who gave which testimony, and the attitudes of local forces against them.In the Ottoman world, the matter of perjury appears conspicuously when the mentioned cases are on the agenda. Undoubtedly, in the cases of “ilhad” and “zendeka” that partly bear characteristic of a catalogue offence in the Ottoman justice mechanism, it is crucial that the community’s testimony nullifies expectations of both case owners and false witnesses.
Keywords: Edirne; zendeka and ilhad; Valihi; Rusheni; false witness